ANALISIS KETERLIBATAN HIDUP MENGGEREJA SISWA SEKOLAH DASAR KOTA BENGKULU DI PAROKI SANTO YOHANES PENGINJIL BENGKULU - Juliana Sriana Sinaga (Bahasa Indonesia, 2022)
This study aims to analyze the involvement of Bengkulu City Elementary School Students in church life. This research was conducted at the St. Yohanes Evangelist Parish Bengkulu from September to October 2021. This research used a qualitative method. The subjects used in this study were Bengkulu City Elementary School Students. Data collection techniques used in this study were in the form of interviews, observations, and questionnaires. The results of the study indicate that there are still many Elementary School Students in Bengkulu City who have not been involved in church life. Some of the obstacles faced by the students were from within, such as: lack of enthusiasm and not knowing the benefits of being involved in church life; while external factors such as: parents who are always busy at work, the distance between the church and the house is quite far, the economic situation is not supportive, and the meeting schedule between activities has not been well coordinated. Based on this fact, the writer recommends the Parish Pastor, Parish Pastoral Council, and parents to work together to give more serious attention to children as the successors of the Church.